2007
DOI: 10.1017/s0021859607007253
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable grassland and livestock management

Abstract: SUMMARYGrasslands are one of the world's major ecosystems groups and over the last century their use has changed from being volunteer leys, or a resource on non-arable land, to a productive resource equal to any crop and managed as such. Many grasslands are now being acknowledged as having a multifunctional role in producing food and rehabilitating crop lands, in environmental management and cultural heritage. However, grasslands across the globe are under increasing pressure from increasing human populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 135 publications
(177 reference statements)
3
66
0
1
Order By: Relevance
“…hunting, fishing, ecotourism; Kemp and Michalk, 2007); (ix) catchment areas for water supply to control runoff and to maintain water quality for urban supply and estuarine and marine environments; and (x) the contribution to the national identity and to cultural and religious aspects of rural societies. In many countries these are important for social stability and social structures (FAO, 2009).…”
Section: The Multifunctional Roles Of Grasslandsmentioning
confidence: 99%
See 1 more Smart Citation
“…hunting, fishing, ecotourism; Kemp and Michalk, 2007); (ix) catchment areas for water supply to control runoff and to maintain water quality for urban supply and estuarine and marine environments; and (x) the contribution to the national identity and to cultural and religious aspects of rural societies. In many countries these are important for social stability and social structures (FAO, 2009).…”
Section: The Multifunctional Roles Of Grasslandsmentioning
confidence: 99%
“…Solutions to such issues are complicated by the need to meet the short-term and long-term needs of those whose livelihoods depend on grasslands. There are more than 800 million in the world with very low income, and an additional 200 million in the more marginalarid and semi-arid areas, who are highly dependent on grasslands for their livelihoods Kemp and Michalk, 2007;McDermott et al, 2010;Ayantunde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During the past 50 years, grasslands have been increasingly managed to support growing agricultural demands (Gibon 2005;Kemp and Michalk 2007). The application of nitrogen (N) to grassland is one of the major management tools farmers have to influence yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, 90% of useable grasslands are degraded because of over-grazing, improper reclamation and adverse effects of droughts exacerbated by climate change (Li 1999;Liu et al 2002;MEP 2006;Li et al 2008;Yang 2010). Many studies have shown that lower stocking rates are necessary for rehabilitating degraded rangelands (Ellison 1960;Hilbert et al 1981;Dyer et al 1986;Kaiser 1998;Kemp and Michalk 2007;Zheng et al 2011). In order to remediate grassland degradation, the government has proposed the 'balancing animals and grass' policy.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have explored the technologies and methods by which herders could reduce livestock numbers and still make profits (Kemp and Michalk 2007;Zhao and Ba 2009;Han et al 2011;Takahashi and Jones 2011;Zheng et al 2011;Yang et al 2012). The Chinese government has also implemented a series of policies to encourage herders to reduce livestock numbers.…”
Section: Introductionmentioning
confidence: 99%